Pengaruh Akuntabilitas Pengelolaan Keuangan Desa Pasca Pemberlakuan Undang-Undang Desa (Studi Kasus pada Gampong Harapan Kota Lhokseumawe) - Mustazir Ramli; Heru Fahlevi (Jurnal Telaah dan Riset Akuntansi, 2016)
This study aims to describe how the mechanisms and forms of accountability in financial management of the village. The study will also describe how the village government capacity in financial management responsibilities of the village with a case study in Gampong Harapan Kota Lhokseumawe. The research design is a case study with primary and secondary data sources. Primary data was collected through interviews and observations, while secondary data obtained by collecting documentation. Analysis of data using interactive data analysis methods, and to assure the validity of the data obtained, the researchers used a data source triangulation techniques and triangulation methods. The results showed that the financial management accountability mechanisms village in the Village of Hope has been realized well. Form of accountability at Gampong Harapan, namely accountability vertical and horizontal accountability. The capacity of the village government hopes very much supported by the existence of the village officials who understand the science of administration and accounting.KEYWORDS : Village Financial Management, Accountability, Capacity village government.